USDA, NIH and FDA Iodine Database of U.S. Foods for Estimating Iodine Intakes. (7th June 2021) - Pehrsson, Pamela; Spungen, Judith; Ershow, Abby; Patterson, Kristine; Roseland, Janet; Gahche, Jaime; Andrews, Karen; Haggans, Carol; Merkel, Joyce
Abstract: Objectives: Data on the iodine content of foods are needed to assess intake and plan dietary guidance. Iodine is central for thyroid function in human growth, reproduction, neurologic development and energy metabolism, and inadequate or excessive intakes can cause thyroid dysfunction and/or disease. Overall, U.S. iodine intake is sufficient, but some women of reproductive age and pregnant women may be at risk for deficiency, as well as people whose dietary patterns do not include iodine-rich foods. Methods: A Special Interest Database (SID) was developed through the collaboration of the Methods and Application of Food Composition Laboratory (USDA), the Food and Drug Administration (FDA), and the Office of Dietary Supplements (NIH). Data for foods and beverages were derived from samples analyzed by USDA and the FDA Total Diet Study; foods included seaweed, fish and other seafood, dairy, iodized salt, eggs, and commercial foods; metadata were captured as varying iodine levels may arise from feed supplementation, iodophor use, and iodine-containing ingredients in processed foods. Samples were analyzed for iodine using inductively coupled plasma mass spectrometry (ICP-MS). Quality control included certified reference materials and secondary in-house controls. Results: The Special Interest Database on Iodine (https://www.ars.usda.gov/northeast-area/beltsville-md-bhnrc/beltsville-human-nutrition-research-center/methods-and-application-of-food-composition-laboratory/mafcl-site-pages/iodine/ ) was released in 2020 and includes food descriptions, means, standard deviations, value ranges, sample sizes, and supporting information for 430 foods. Foods continue to be analyzed for iodine and added to the database. In addition, iodine intakes of the U.S. population are being calculated by mapping the iodine content of foods to food consumption data from the 2014 U.S. National Health and Nutrition Examination Survey (NHANES) and eventually more recent NHANES dietary data. Conclusions: The SID on Iodine and the mapped NHANES data provide needed information to monitor iodine status and develop dietary guidance for the general U.S. population and vulnerable subgroups. Furthermore, the database can provide a valuable tool for other research programs and clinical applications in iodine nutrition. Funding Sources: NIH Office of Dietary Supplements.